An Influence Of Live Streaming And Trust On Impulse Buying Among Shopee Users In Medan City - Lovisca Stevany Sembiring; Haryaji Catur Putera Hasman; Yuni Syahputri (Jurnal Ekonomi, 2024)
This research aims to described the effect of live streaming and trust on impulse buying among Shopee application users in Medan City. This research uses quantitative and associative methods. The total population is 869,609 residents spread across 5 sub-districts as representatives of Medan City. In determining the sample, the author used Slovin's theory with a sample of 100 and the sample collection technique used was non-probability sampling and used snowball sampling to determine the sample. The data analysis technique uses multiple linear regression analysis. Based on the research results, it shows that (1) the live streaming variable has a significant effect on impulse buying among Shopee application users in Medan City, (2) the trust variable has a significant effect on impulse buying among Shopee application users in Medan City, (3) the live streaming variable, trust simultaneously has a significant effect on impulse buying among Shopee application users in Medan City.